Optimizing Temporal Capital: How Big Tech Imagines Time as Auditable. - Erickson, Ingrid; Wajcman, Judy (American Behavioral Scientist, 2023)
The belief that technology can be profitably employed to control and manage time has a long history. In this article we show how electronic calendaring systems have become emblematic of the contemporary vision of mastering time, codifying a distinctive quantitative orientation to time. Drawing on interviews with calendar designers at four prominent software development companies, we explore the quest among knowledge workers in Silicon Valley to embed a culture of temporal optimization through the use of calendaring software. Their collective response to this issue reveals that there is a specific kind of technoscientific world being developed: one fixated with solving the problem of time scarcity in contexts organized around maximizing productivity. Furthermore, this world is increasingly embracing the power of predictive data analytics and artificial intelligence. Yet, rather than being the progressive act that many Silicon Valley designers believe they are engaging in, this move toward automating time is the latest in a series of long-standing moral attempts to subject time to a particular brand of rationalization. This orientation to, and valorization of, the fast-paced, full life requires incessant performance on our part and the relentless pursuit of self-enhancement. In other words, positing that time has now become fodder for pattern recognition, we argue that calendaring software configures time events as auditable data that is ripe for accounting in the service of both old and new forms of socially-constructed optimization. We conclude by drawing out the implications of treating time as auditable data, most importantly, that it reinforces asymmetrical relations of power and devalues relations of care.